GEN Z’S PERCEPTION OF ORGANIZATIONAL ALIGNMENT AND ITS IMPACT ON EMPLOYEE ENGAGEMENT - Sharma, Ananya; Kapoor, Meera (International Journal of Allied Research in Economics (IJARE), 2023)
As members of Generation Z (Gen Z) become integral parts of the contemporary workforce, characterized by their tech-savvy nature, they bring distinct perspectives and expectations to the workplace. This paper aims to comprehensively explore the factors influencing Gen Z’s engagement in the workplace and elucidate the correlation of these factors with overall employee engagement. The foundation of this research lies in a thorough literature review, which informs the development of hypotheses. Leveraging insights from existing research papers, this study employs MS Excel for data analysis, utilizing statistical tools such as correlation coefficient and regression. The findings reveal a positive correlation between identified factors and both organizational performance and employee engagement among Gen Z. Notably, career development and rewards and recognitions emerge as pivotal factors. The paper underscores the necessity for policy adaptations to accommodate the unique expectations of this emerging workforce. Failure to address these evolving dynamics may impede companies’ ability to effectively attract, retain, and engage Gen Z in the evolving workplace landscape